Antibacterial activity of red betel (Piper crocatum) leaf methanolic extracts aginst methicillin resistant Staphylococcus aureus - Tristia Rinanda; . Zulfitri; Desi Maharani Alga (Syiah Kuala University, 2012)
Red betel (Piper crocatum) is one of traditional medicine that has antibacterial activity. This research was conducted to determine the antibacterial activity of the methanol extract of red betle leaves against growth of Methicillin Resistant Staphylococcus aureus (MRSA). This research used Completely Randomized Design (CRD) method with 5 treatment groups consist of red betle leaves extract with concentration 150 mg/mL, 300 mg/mL, 450 mg/mL, 600 mg/mL, and negative control (sterile water) with 4 times repetition. The methanol extract of red betle leaves was obtained by maceration technique using methanol 96% as solvent. Antibacterial activity test conducted with Kirby Bauer disc diffusion method. Data of this research were analyzed by ANOVA followed by Duncan Test. The results showed that red betel leaf extracts in concentration 150 mg/mL, 300 mg/mL, 450 mg/mL, 600 mg/mL provide average inhibition zone respectively 9,0 mm, 11,2 mm, 13,6 mm and 15,7 mm. The result showed that red betel leaf extracts in tested concentration showed antibacterial activity against MRSA. The higher concentration of extract, the greater inhibition area was formed.